Efficacy of Stellate Ganglion Blockade in Managing Electrical Storm: A Systematic Review - Meng, Lingjin (JACC Clin Electrophysiol, 2017)
BACKGROUND: The efficacy of percutaneous stellate ganglion block (SGB) for managing electrical storm (ES) is not well understood. OBJECTIVE: To characterize the efficacy of SGB as a treatment for ES. METHODS: We conducted literature searches using PubMed/Medline and Google Scholar, for mixed combinations of terms including “stellate ganglion block”, *ganglion block (ade)”, “sympathetic block (ade)” and “arrhythmia”, “ventricular arrhythmia (VA)” or “tachycardia" (VT), "ventricular fibrillation" (VF), "electrical storm”. Inclusion criteria were presentation with guideline-defined ES and treatment with SGB. Exclusion criteria: presentation with any supraventricular arrhythmia, VA without ES, or surgical sympathectomy. Studies lacking basic demographic data, arrhythmia description, and outcomes were excluded. RESULTS: Of 3,374 publications reviewed, 38 patients from 23 studies met study criteria (52 ± 19.1 years, 11 F, 17 with ischemic cardiomyopathy). Anti-arrhythmics were used in all patients. Mean Left ventricular ejection fraction was 31 ± 10%. ES was triggered by acute myocardial infarction in 15 patients and QT prolongation in 7 patients. The most common local anesthetic used for SGB was bupivacaine (0.25–0.5%). SGB resulted in a significant decrease in VA burden (12.4±8.8 vs. 1.04±2.12 episodes/day, p< 0.001) and number of external and ICD shocks (10.0±9.1 vs. 0.05±0.22 shocks/day, p< 0.01). Following SGB, 80.6% of patients survived to discharge. CONCLUSION: SGB is an effective acute treatment for ES. However, larger prospective randomized studies are needed to better understand the role of SGB in ES and other VAs.